Caribbean business to business guide. The official business guide of Puerto Rico / Group Sales & Service (1993)
Alphabetical index by business categories, by company name, P. R. Caribbean islands general information, company listing by office buildings, company listing by industrial parks, key business groups, communications/media, construction/real estate, environmental services, industrial / office supplies & computers, insurance.